Effects of torch ginger essential oil on pathogens, quality and storage of dragon fruit [Hylocereus polyrhizus (Weber) Britton & Rose] - Mohd Aziz, Khawarizmi (2018)
Dragon fruit is an exotic fruit which exhibits a non-climacteric pattern of respiration. This indicates it needs to be harvested from the tree when it is fully ripe since it cannot ripen after harvest. This had become a limiting factor for this fruit to have longer storage life. Dragon fruit also very susceptible to postharvest disease during storage. In addition, the bract of this fruit is easily dried and turn to brown few days after harvest which cause losses to its appearance. Thus, to overcome this problem, torch ginger leaf’s essential oil (EO) was used as a natural antimicrobial agent for dragon fruit to extend the storage life as well as to maintain the fruit quality. The aim of this research was to evaluate the antimicrobial activity of torch ginger leaf’s EO towards the isolated pathogen from dragon fruit and to investigate the effect of this EO incorporated into tapioca starch as edible coating on dragon fruit. In the first study, pathogen was isolated and identified from diseased dragon fruit. Second study was the continuation of the first study, where EO antifungal effect was tested against isolated pathogens in vitro. The experiment was conducted using completely randomized design. Bipolaris cactivora and Fusarium incarnatum were found to be the causal pathogen for dragon fruit during storage. Results of poison agar study portray that 0.5% EO was able to inhibit 60.22% of B. cactivora mycelium growth compared to 38.11% of F. incarnatum. However, the conidia germination study reflect that B. cactivora conidia were more resistant to EO where it showed higher germination as compared to F. incarnatum. Spore count showed that 0.5% of EO was able to completely stop the spore production of F. incarnatum while the same concentration only reduces the spore of B. cactivora. The third experiment was done using completely randomized design in factorial arrangement (8 treatments x 3 weeks of storage). Different concentration of EO was incorporated into tapioca starch as coating for dragon fruit and stored at 5 ± 2 ºC for three weeks at 80 ± 5% relative humidity. The analysis was done at weekly interval where various physico-chemical analysis were analysed. Bract visual quality was found to be better with low concentration of EO which is the same for peel disease severity (DS) where 1% EO treatment showed lower DS. Water loss was found to be lower in coated fruit. Peel firmness and respiration rate were found to react differently towards different coating treatments. Glossiness was found to be higher in higher concentration of EO used. Ascorbic acids did not respond to treatments applied. However, other antioxidant assays were found to show higher concentration of antioxidant in fruit treated with 1% EO compared to control. Overall, findings in both in vitro and in vivo study it can be concluded that 2% EO was effective in controlling most parameters studied in in vitro study while fruit coated with 1% EO was found to be potentially beneficial to improve the postharvest storage of this fruit as portrayed by the result in in vivo study.